Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1017/dsd.2020.64
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Effect of Self-Efficacy and Influencers on Design Team Performance

Abstract: Social media influencers (SMI) are gaining interest and many are studying their influence on the online audience, little is known about the role played by them in offline teams. One such attempt to study the effect of influencers in co-design team is presented in this paper, where individuals who are confident in their abilities drive the team process. Thus, self-efficacy is considered for determining influencer behaviour. Results expose the relationship between self-efficacy and influencer status on the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…High self-efficacy individuals also had an influence on other high self-efficacy individuals hence, it conforms to Singh et al (2020). It further supports the assumption that self-efficacy could be one of the factors affecting the I ∝ SE.…”
Section: Validating the Assumptionsupporting
confidence: 77%
“…High self-efficacy individuals also had an influence on other high self-efficacy individuals hence, it conforms to Singh et al (2020). It further supports the assumption that self-efficacy could be one of the factors affecting the I ∝ SE.…”
Section: Validating the Assumptionsupporting
confidence: 77%
“…This is due to their increase in intrinsic motivation that increases their self-efficacy. It was also found that individuals with high self-efficacy are less likely to be demotivated when other team members do not select their ideas [35]. Taking these findings into account, the agents in the model demonstrates similar behavior, where increase/decrease in an agent self-efficacy depends on their current state of self-efficacy.…”
Section: Learning From Experiencementioning
confidence: 80%
“…Increase in intrinsic and extrinsic motivation increases self-efficacy [24]. In other studies state that individuals contribute more in idea generation when the team accepts ideas from them [35]. This is due to their increase in intrinsic motivation that increases their self-efficacy.…”
Section: Learning From Experiencementioning
confidence: 94%
“…If co-design is considered as a social process (Cross and Cross, 1995), the factors affecting the interactions, roles and relationships among the team members should be considered. It is known that the degree of influence perceived by team members from each other determines team performance (Singh et al, 2020b); trust in teams is responsible for work effectiveness (Costa, 2003) and factors affecting idea selection (like agreement in solutions) are crucial to study (Lindley et al, 2017). Moreover, the prior acquaintance between individuals (i.e.…”
Section: Familiarity Bias In the Social Variablesmentioning
confidence: 99%